Removal of Acid Red 88 from an Aqueous Solution Using Kaolinite Clay by Adsorption Process - Dadebo, Derrick; Obura, Denis (East African Nature and Science Organization, 2022)
Dyes are hazardous contaminants normally found in industrial wastewaters necessitating costly and complex technologies for their removal. In this study, clay was used as an adsorbent in the removal of anionic acid red 88 (AR 88) dye from industrial wastewaters by adsorption. The dye removal efficiency and adsorption capacity of clay was studied by batch experimentation with respect to parameters of dye initial concentration, clay dosage, contact time, and pH. The dye removal efficiency of AR 88 improved with increasing dosage (r 0.9826, p < 0.05), contact time (r 0.9821, p 0.000683) and decreased with increasing initial concentration (r - 0.9168, p 0.02844) and pH (r -0.9666, p 0.007297) of the solution. At initial AR dye concentration of 100 mg/L, the removal efficiency and adsorption capacity of 89.7% and 4.38 mg/g, respectively were achieved after equilibrium time of 30 minutes under the optimum conditions of pH 2 and clay dosage 20 g/L. The study thrived in applying an efficient and low-cost adsorbent that could be used as a substitute to high-cost conventional commercial adsorbents in treating industrial wastewater with AR dye coloration